A next-generation LHC heavy-ion experiment - Adamová, Dagmar; Arslandok, Mesut; Bergmann, Luisa; Flörchinger, Stefan; Glässel, Peter; Köhler, Markus Konrad; Klewin, Sebastian; Kroesen, Martin; Leardini, Lucia; Pachmayer, Yvonne C.; Pawlowski, Jan M.; Reygers, Klaus; et al. (Arxiv, 2019)
The present document discusses plans for a compact, next-generation multi-purpose detector at the LHC as a follow-up to the present ALICE experiment. The aim is to build a nearly massless barrel detector consisting of truly cylindrical layers based on curved wafer-scale ultra-thin silicon sensors with MAPS technology, featuring an unprecedented low material budget of 0.05% X$_0$ per layer, with the innermost layers possibly positioned inside the beam pipe. In addition to superior tracking and vertexing capabilities over a wide momentum range down to a few tens of MeV/
Author list: D. Adamová, M. Arslandok, L. Bergmann, S. Floerchinger, P. Glässel, M.K. Köhler, S. Klewin, M. Kroesen, L. Leardini, Y. Pachmayer, J. Pawlowski, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, H. Soltveit, J. Stachel, D.F. Weiser, B. Windelband [und weitere]
Gesehen am 14.02.2019